The “Wild” Continent? Some Discussions on the Anthropocene in Antarctica - Zarankin, Andrés; Salerno, Melisa Anabella (Journal of Contemporary Archaeology)
As members of an international research project investigating the historical archaeology of the first human settlements in Antarctica, we are interested in the distinguishing features of the anthropocene in the last continent to be known by human beings. Our project understands that, despite what is commonly said, the distinctive features of Antarctica do not rest on its "wilderness" or in its return to a certain "state of wilderness" (considering that the human history of the continent could have started differently). From our standpoint, its present distinctive features are nothing but a product of the historical strategies defining the human expansion and interaction with the continent throughout the 19th, 20th and 21st centuries. Fil: Zarankin, Andrés. Universidade Federal Do Minas Gerais. Departamento de Sociología y Antropología; Brasil. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Salerno, Melisa Anabella. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Saavedra 15. Instituto Multidisciplinario de Historia y Ciencias Humanas; Argentina